STUDI GUNUNG API TERSIER: SEBARAN PUSAT ERUPSI DAN PETROLOGI DI PEGUNUNGAN SELATAN YOGYAKARTA - HARTONO , GENDOET
Tertiary volcanic rocks in the Southern Mountains, Yogyakarta are distributed from Parangtritis in the west until Wonogiri in the east and cover an area of 1,625 km2. The aim of the research is to identify volcanic bodies including their eruption centers and petrology of the volcanic rocks. The research is based on a principal geology of The present is the key to the past with study approaches from geomorphology and petrology. In the research area there are six volcanic terrains identified, namely Khuluk Parangtritis, Khuluk Sudimoro Mangunan, Khuluk Panggung, Khuluk Wediombo, Bregada Baturagung-Bayat and Bregada Gajah Mungkur-Wonogiri. These volcanoes are distributed from SSW-NNE, except for Khuluk Wediombo that is isolated in the south. Based on K-Ar dating analyses the volcanic activity began in Paleocene (58,58 plus minus 3,24 Ma) till Oligo-Miocene (33,15 plus minus 1,00 Ma - 24,25 plus minus 0,15 Ma) on land up to shallow marine environments, probably as island volcanoes or volcanoes in the beach. Volcanostratigraphic units of Khuluk Parangtritis, Khuluk Mangunan-Sudimoro and Khuluk Panggung are composed of calc-alkaline basalt-andesite (53,2 - 54,7 % SiO2; 0,93 - 1,11 % K20) while Khuluk Wediombo consists of tholeiitic andesite (58,87 % SiO2; 0,61 % 1(20). Volcanic rocks from Bregada Baturagung and Bregada Gajah Mungkur are composed of Calc-Alkaline basalt-dacite (48,16 - 67,1 % SiO2; 0,84 - 2,65 % K20). Compositions of basalt to andesite of lava flows and volcanic breccias were produced during construction phases of composite volcanoes. Whereas andesite to dacite pumice-rich volcaniclastic rocks indicate a very explosive eruption during caldera formation. Implications from this research are to propose the application of volcano stratigraphic units in Tertiary volcanic rocks and to support geologic explorations of volcanogenic minerals.